Active deformation in the northern Sierra de Valle Fertil, Sierras Pampeanas, Argentina - Ortiz, Gustavo Federico (2015)
The Western Sierras Pampeanas region in the San Juan Province is characterized by thick-skinned deformation with approximately NeS trending ranges of average heights of 2500 m and a high frequency occurrence of seismic activity. Its location to the east of the mainly thin-skinned tectonics of the Argentine Precordillera fold-and-thrust belt suggests that at 30S, deformation is concentrated in a narrow zone involving these two morphostructural units. In this paper, we present new apatite (UeTh)/He results (AHe) across the northern part of the Sierra de Valle Fertil (around 30S) and analyze them in aframework of thermochronologic available datasets. We found Pliocene AHe results for Carboniferous and Triassic strata in the northern Sierra de Valle Fertil consistent with the hypothesis of recent cooling and inferred erosional denudation concentrated along the northern end of this mountain range. Ouranalysis shows that this northern region may have evolved under different conditions than the central part of the Sierra de Valle Fertil. Previous studies have observed AHe ages consistent with Permian through Cretaceous cooling, indicating the middle part of the Sierra de Valle Fertil remained near surfacebefore the Pampean slab subduction flattening process. Those studies also obtained ~5 My cooling ages in the southern part of the Sierra de Valle Fertil, which are similar to our results in the northern end of the range. Taken together, these results suggest a pattern of young deformation in the northern and southern low elevation ends of the Sierra de Valle Fertil consistent with regions of high seismic activity, and Quaternary active faulting along the western-bounding thrust fault of the Sierra de Valle Fertil.